The Character of Responsibility in Musim Semi Itu Bernama Al-Qur’an by Aulia Musla - Amarasuli, Shalsa; Samhati, Siti; Sumarti, Sumarti; Ariyani, Farida; Rusmito, Nurlaksana Eko (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The study in this research focuses on the analysis and description of the character of responsibility contained in the book Spring It's Named Al-Qur'an by Aulia Musla. The research data are sentences in the dialog and narration of the book Spring Named Al-Qur'an that contain the character of responsibility. Data collection is done by reading and recording techniques. The data analysis technique used is descriptive analysis. The results of the study show that the character of responsibility in the book is reflected in the form of responsibility towards God, social responsibility, and responsibility towards oneself. First, the character of responsibility towards God is reflected in the attitude of the character who invites to murojaah and be grateful for all the blessings that have been bestowed by Allah SWT. Second, the character of social responsibility is reflected in the attitude of Aunt Ida who likes to share and Altan who loves cats as living creatures. Third, the character of responsibility towards oneself is reflected in the attitude of Altan who takes the initiative to find solutions to solve problems and is able to take responsibility for his actions